Factors Related to Psychological Help-Seeking Behavior among First-Year College Student - Astuti, Cici Siti Widya; Pramukti, Iqbal; Widianti, Efri (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2021)
AbstractIntroduction. Psychological Help-Seeking Behavior is an action taken in seeking psychological help from others to solve the problem at hand. Objectives. This study aims to determine factors related to psychological help-seeking behavior among first-year college students. Methods. This study is a descriptive-correlation study with an approach cross-sectional, the sample was taken using proportionate stratified random sampling, with a total of 144 participants based on the G-Power calculation. The instruments used are General Help-Seeking Questionnaire (GHSQ) and Actual Help Seeking Questionnaire (AHSQ), data analysis using univariate and bivariate (chi-square). Results. In this research, there is a relationship between age factor and gender factor with psychological help-seeking behavior with a p-value ( 0.05). Discussions. Most of the first-year students perform psychological help-seeking behavior in the future and currently, while other factors in this research did not have a significant relationship both in the future, past and present, this can happen due to unbalanced number of sample proportions.AbstrakPendahuluan. Perilaku Mencari Bantuan psikologis merupakan suatu tindakan yang dilakukan dalam mencari bantuan psikologis kepada orang lain dengan tujuan untuk memecahkan masalah yang sedang dihadapi. Tujuan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan perilaku mencari bantuan psikologis pada mahasiswa tingkat pertama. Metode. Penelitian ini merupakan penelitian deskriptif-korelasi dengan pendekatan cross-sectional, pengambilan sampel menggunakan proportionate stratified random sampling, dengan jumlah partisipan sebanyak 144 berdasarkan perhitungan G-Power. Instrumen yang digunakan adalah General Help Seeking Questionnaire (GHSQ) dan Actual Help Seeking Questionnaire (AHSQ), analisa data menggunakan univariat dan bivariat (chi-square). Hasil. Dalam penelitian ini terdapat hubungan antara faktor usia dan jenis kelamin dengan perilaku mencari bantuan psikologis dengan nilai p value ( 0.05). Diskusi. Sebagian besar mahasiswa tingkat pertama melakukan perilaku mencari bantuan psikologis dimasa depan dan saat ini, sedangkan faktor-faktor lain pada penelitian ini tidak ada hubungan yang signifikan baik diwaktu masa depan, masa lalu dan masa saat ini,Â  hal ini dapat terjadi karena berdasarkan data demografi jumlah proporsi sampel tidak seimbang.Â Â